2017
DOI: 10.1038/s41559-017-0236-1
|View full text |Cite
|
Sign up to set email alerts
|

A sex-chromosome inversion causes strong overdominance for sperm traits that affect siring success

Abstract: Male reproductive success depends on the competitive ability of sperm to fertilize the ova, which should lead to strong selection on sperm characteristics. This raises the question of how heritable variation in sperm traits is maintained. Here we show that in zebra finches (Taeniopygia guttata) nearly half of the variance in sperm morphology is explained by an inversion on the Z chromosome with a 40% allele frequency in the wild. The sperm of males that are heterozygous for the inversion had the longest midpie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(116 citation statements)
references
References 72 publications
5
107
1
Order By: Relevance
“…Second, the zebra finch might in fact have a very specific architecture of genes influencing sperm morphology. Two recent studies found that these genes are located on the Z chromosome and, due to strong linkage disequilibrium, effectively work as one “supergene” (Kim et al., ; Knief et al., ). Consequently, the phenotype largely depends on whether an individual is a homozygote or a heterozygote for normal and inverted haplotypes (Kim et al., ; Knief et al., ) which may underlie the high evolvability and heritability of sperm morphology, as well as the negative genetic correlation between some sperm sections (Birkhead et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the zebra finch might in fact have a very specific architecture of genes influencing sperm morphology. Two recent studies found that these genes are located on the Z chromosome and, due to strong linkage disequilibrium, effectively work as one “supergene” (Kim et al., ; Knief et al., ). Consequently, the phenotype largely depends on whether an individual is a homozygote or a heterozygote for normal and inverted haplotypes (Kim et al., ; Knief et al., ) which may underlie the high evolvability and heritability of sperm morphology, as well as the negative genetic correlation between some sperm sections (Birkhead et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be the case in the only studied bird species, the zebra finch Taeniopygia guttata , where the heritability of total sperm length was estimated to be 0.63 ± 0.11 SE (Mossman et al., ). Recent genetic studies in the zebra finch have shown that genes underlying sperm morphology are located on the Z chromosome which has a low recombination rate due to a large chromosomal inversion in some haplotypes (Kim et al., ; Knief et al., ). Consequently, these linked genes act as one “supergene” with a major effect on sperm phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…; Knief et al. ). We also evaluated variation in tail length (the part of flagellum not wrapped by the midpiece), but the association with sperm performance remains unclear for this trait.…”
Section: Methodsmentioning
confidence: 98%
“…The length of the sperm head (including acrosome), the midpiece, and the tail of each sperm were later measured to the nearest 0.1 μm using QuickPhoto Industrial software (Olympus) following standard protocol (e.g., Knief et al. ). Total sperm length was calculated as the sum of these three components.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, a study of 40 bird species found significant associations for all morphometric traits examined with sperm velocity, including midpiece length, flagellum length and the ratio of midpiece:flagellum length (Lüpold et al, ). Perhaps the most conclusive evidence yet comes from the zebra finch, in which midpiece length and flagellum length are genetically correlated (Birkhead, Pellatt, Brekke, Yeates, & Castillo‐Juarez, ) and associated with sperm velocity, mediated by an inversion on the Z chromosome (Kim et al, ; Knief et al, ). Moreover, zebra finches subject to oxidative challenge produce slower sperm with shorter midpieces (Tomáŝek, Albrechtová, Nĕmcová, Opatová, & Albrecht, ).…”
Section: Discussionmentioning
confidence: 99%